Ohio materials, Anthony F. C. Wallace Papers - Wallace, Anthony F. C., 1923-2015 (1951)
The Anthony F. C. Wallace Papers are a vast collection of materials relating to Wallace's work at the intersection of anthropology, psychology, and history. Though further research might yield more results, approximately 20 items directly pertaining to the peoples Wallace called the "Ohio tribes" have been identified. Most of the materials are are located in Series IX. Indian Claims, and relate to Wallace's work as a researcher and expert witness on behalf of Native American land claims. They include copies of and extracts from primary and secondary sources, research notes, tribal histories, court dockets, trial memoranda, and correspondence. There are also research notecards with notes from primary and secondary sources in Series III. Notecards. Series IV. Works by Wallace, A. Professional contains Wallace's Ohio Indians and Six Nations Indian claims reports to lawyers detailing Haudenosaunee, Shawnee, Delaware, Wyandot, Odawa, Miami, and Illinois occupation of Ohio from 1649-1794. In the same series, B. Creative Writing contains a draft of what Wallace called his "Ohio Novel," a fictionalized account of the murder of John Armstrong, Woodworth Arnold, and James Smith by Delawares in 1744 and subsequent events through the Seven Years' War. However, most of the Ohio items pertain to claims to Ohio lands by the Delaware, Shawnee, and Haudenosaunee (formerly Iroquois), and there is overlap with the entries for each of those groups. See the finding aid for a detailed discussion of Wallace's long and varied career, and for an itemized list of the collection's contents.